Memperkenalkan Algoritma dan Berpikir Algoritmik kepada Siswa Sekolah Dasar Menggunakan CS Unplugged - Sondakh, Debby Erce; Pungus, Stenly Richard; Maringka, Raissa C; Tangka, George M. W (Servitium Smart Journal, 2024)
A community service was conducted aiming at introducing the concept of algorithms and algorithmic thinking to elementary school students, using the Computer Science Unplugged approach. Two main activities, "Sorting Network" and "Move It, Move It," were implemented. A total of 35 students from elementary schools in rural areas in North Sulawesi, where computer equipment is not available. The assessment of the success of these activities was based on behavioral observations, student participation, and their feedback on the activities. The results of this activity showed an increase in students' understanding of the concept of algorithms and strengthening their ability to apply algorithmic thinking. In addition, this activity also succeeded in increasing students' interest in computer science and demonstrating the importance of interactive learning in basic education.